Instructional design: Integration of the Q10 platform into the ADDIE model - Almidón Ortiz, Carlos Alcides; Coronado Pérez de Almidón, Edith Miriam; Ormachea Mejía, Mario Jesús; Almidón, Elescano Angel (Revista de Ciencias Sociales, 2025)
Instructional design is intended to create effective and efficient experiences within education, adapting to the growing demands of the digital society and accelerated virtualization, a product of the COVID-19 pandemic. In this order of ideas, the article analyzes how the integration of the Q10 platform in the ADDIE model can optimize the instructional design, providing a flexible and efficient structure for the management and creation of educational materials. Methodologically, this is a qualitative type of research, with application of the documentary exploration method. Among the main findings, it is highlighted that the ADDIE model, based on analysis, design, development, implementation and evaluation, is a proven alternative for the design of educational programs, while the Q10 platform provides a series of advanced tools for educational management, which, when integrated to the ADDIE model, improves virtual education programs. It is concluded that the integration of the Q10 platform with the ADDIE model offers a series of holistic solutions to improve the instructional design, making the learning experience more autonomous and focused on student needs.